EFFECT OF PERMEABILITY ANISOTROPY ON FORCED CONVECTION THERMAL -HYDRODYNAMICS OF ENTRANCE AND DEVELOPED FLOW REGIMES IN POROUS SATURATED CIRCULAR TUBE - AKOWANOU, Christian; DEGAN, GÉRARD; PRODJINONTO, Vincent (My University, 2016)
Forced convective flow through anisotropic porous saturated circular tube was analysed to determine the entrance length to the hydrodynamic flow. The porous medium saturated with an incompressible viscous fluid was characterized by anisotropy permeability ratio, inclination angle of the principal axes and Prandtl number. The flow field was a succession of two distinct flow regions, the entrance region followed by fully developed flow regime. The boundary-layer regime prevailing at the thermal entrance region was analysed by integral relations approach, and analytical expressions of the entrance length, wall friction and heat transfer rate were obtained. Limiting cases for flow applicable to low and high porosity media were also observed. The anisotropic properties of the porous medium were significant where permeability ratio was either greater or less than 1.
Keywords: Forced convection; Porous medium; Hydrodynamic flow field; Anisotropy Permeability ratio; Wall friction